2022
DOI: 10.1002/ejoc.202200116
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Multispin Systems with a Rigid Ferrocene‐1,1′‐diyl‐Substituted 1,3‐Diazetidine‐2,4‐diimine Coupler: A General Approach (Eur. J. Org. Chem. 7/2022)

Abstract: The Cover Feature shows a beautiful sunrise metaphorically representing the boundary between chemistry and physics, the interaction of which has paved the way for the synthesis of a biradical with a ferrocene‐derived inflexible bridging moiety. This is a versatile route and could be used to prepare weakly coupled biradicals with different spin‐bearing groups and with a redox‐active ferrocene part. More information can be found in the Research Article by E. V. Tretyakov et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This trend is related to the synthesis and study of the properties of complexes in which a gold atom is bonded to a paramagnetic moiety. The first examples of such complexes are specific derivatives of a paramagnetic organogold unit with a phosphine ligand (PR 3 ) of the NN–Au–PR 3 type (where NN is a deprotonated nitronyl nitroxide moiety, i.e., 4,4,5,5-tetramethylimidazoline-3-oxide-1-oxyl). It has been revealed that they have unique redox properties and can serve as an attractive cross-coupling reagent for introducing the NN group into a reaction with aryl iodides and activated aryl bromides. , …”
Section: Introductionmentioning
confidence: 99%
“…This trend is related to the synthesis and study of the properties of complexes in which a gold atom is bonded to a paramagnetic moiety. The first examples of such complexes are specific derivatives of a paramagnetic organogold unit with a phosphine ligand (PR 3 ) of the NN–Au–PR 3 type (where NN is a deprotonated nitronyl nitroxide moiety, i.e., 4,4,5,5-tetramethylimidazoline-3-oxide-1-oxyl). It has been revealed that they have unique redox properties and can serve as an attractive cross-coupling reagent for introducing the NN group into a reaction with aryl iodides and activated aryl bromides. , …”
Section: Introductionmentioning
confidence: 99%